Value chain integration of the Western Balkan countries and policy options for the post-COVID-19 period - Oliver Reiter; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2021)
In this policy brief, we study the development of trade integration, specifically the participation in global value chains, of the Western Balkan countries. Using a multi-country input-output Database, called the 'wiiw MC IOD', we first analyse in a descriptive way the trends in economic integration by looking at forward and backward linkages. Second, we apply a gravity model to accurately pin down the effects of trade integration. The results show that potential EU membership and the earlier Stabilisation and Association Agreements (SAAs) boost trade flows between the new trading partners. These agreements affect particularly the forward linkages and thus support economies to sell their products both directly and indirectly on global markets. This suggests that the Western Balkans should focus their efforts on achieving the maximum possible level of economic integration with the EU even before full accession, including greater access to the EU budget, joining the EU Customs Union and expanding the existing SAAs. Also, EU support for the Western Balkans amid the COVID-19 crisis should be stepped up in order to keep the countries on track for EU integration. More investment in regional infrastructure has the potential to make near-shoring from, for example, Germany and Austria more likely in a post-COVID-19 world.
Keywords: F15; R15; D57; 330; Western Balkans; input-output; global value chain integration